2016
DOI: 10.2119/molmed.2015.00210
|View full text |Cite
|
Sign up to set email alerts
|

Novel Targeted Therapy for Precursor B-Cell Acute Lymphoblastic Leukemia: Anti-CD22 Antibody-MXD3 Antisense Oligonucleotide Conjugate

Abstract: The exponential rise in molecular and genomic data has generated a vast array of therapeutic targets. Oligonucleotide-based technologies to down regulate these molecular targets have promising therapeutic efficacy. However, there is relatively limited success in translating this into effective in vivo cancer therapeutics. The primary challenge is the lack of effective cancer cell-targeted delivery methods, particularly for a systemic disease such as leukemia. We developed a novel leukemiatargeting compound com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 67 publications
(90 reference statements)
0
23
0
Order By: Relevance
“…Frozen whole cell pellets were prepared for western blotting as described previously ( 11 ). Briefly, cell pellets were denatured and boiled, run on a 4–20% Tris-Glycine SDS-PAGE gel, and transferred to a nitrocellulose membrane using a wet transfer system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frozen whole cell pellets were prepared for western blotting as described previously ( 11 ). Briefly, cell pellets were denatured and boiled, run on a 4–20% Tris-Glycine SDS-PAGE gel, and transferred to a nitrocellulose membrane using a wet transfer system.…”
Section: Methodsmentioning
confidence: 99%
“…Since monotherapy does not work for most cancers, an ideal therapy should include multiple molecular-targeted approaches. Previously, we identified the transcription factor MXD3 as a novel target for precursor B-cell acute lymphoblastic leukemia (preB ALL) ( 9 11 ). MXD3 is a member of the family of Mad proteins that interact with Max proteins ( 12 ) and is reported to play a role in medulloblastoma tumorigenesis ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, intramuscular injection enabled superior levels of target engagement in a model of peripheral artery disease, with muscular regeneration due to myostatin knockdown observed with microgram-scale injections. While this Fab'-based study utilized structural cystines for conjugation, other therapeutic antibody-oligonucleotide conjugation systems not yet described in this section have been reported, including two oncology examples which applied two-step conjugations for azide-labeling the antibody which were then treated with cyclooctyne-appended ASOs to generate the conjugates [121,122]. Other antibody-oligonucleotide conjugation methods beyond the scope of this review (i.e., for immuno PCR applications, pre-targeted radiotherapy, or those which utilize non-covalent heterogeneous complexes) have been recently reviewed [109].…”
Section: Nucleic Acid Conjugatesmentioning
confidence: 99%
“…Recent research efforts have focused on new cellular surface targets like CD27 44 and EphA3 61 , as well as improving cancer eradication though development of antibody drug conjugates for CD22 62 . Anti-CD22 antibody therapies have arguably been the most successful, and clinically translatable in treating ALL and other leukemias and lymphomas.…”
Section: Engineered Antibodies Enzymes and Antibody-drug Conjugamentioning
confidence: 99%
“…Since upon binding with CD22, the antibody therapy is endocytosed, CD22 antibodies are an intriguing drug delivery platform for drugs with intracellular actions. Satake et al used monoclonal anti-CD22 antibodies to traffic antisense oligonucleotides for inhibiting translation of MYC-associated factor X (MAX) dimerization protein 3 (MXD3), an important transcription factor involved in preB-cell acute lymphoblastic leukemia 62 . Results of their preclinical study showed that the conjugate successfully trafficked the oligonucleotides to the leukemia cells without off target effects and at one-twentieth of the dose required for similar effects from anti-CD22 monoclonal antibody therapy alone 6263 .…”
Section: Engineered Antibodies Enzymes and Antibody-drug Conjugamentioning
confidence: 99%